SAR image quality metrics with respect to Super-Resolution - Vihavainen, Jami (My University, 2026)
Synthetic aperture radar is a type of radar imaging technique, and it can produce high-resolution images independently of weather conditions. Its ability to operate in all environmental conditions makes it useful for a variety of applications. However, synthetic aperture radar imagery has a few typical features that cause distortion and affect human perceptibility of the image. The distortions such as speckle, layover and diffusion degrade the overall image quality and complicate the interpretation of an image. To address these challenges, multiple enhancement methods have been developed, varying from basic filtering to deep learning-based super-resolution models. Evaluating the effectiveness of such methods is vital and for that purpose, several image quality assessment metrics have been developed. However, many of these metrics created are intended for optical imagery and they do not translate well to synthetic aperture radar imagery due to the nature of the imaging methodology. This thesis focuses on investigating image quality assessment methods and metrics in the context of synthetic aperture radar super-resolution images. The research is done by following the guidelines of iterative literature review, which operates by dividing the study into iteratively executed cycles. The main idea is to include and exclude sources in iterative fashion by proceeding further into each source as rounds go by. This methodology makes it possible to go through many existing research in timely manner. The search is done using keywords, and each subtopic is done separately. The sources that emerge during this process, are further categorised by their respective subtopics. The findings suggest that many of the existing metrics struggle with synthetic aperture radar-specific disruptions, and that no individual metric can assess synthetic aperture radar super-resolution image quality effectively. This is due to the variety of applications of synthetic aperture radar imagery and their specific needs in the context of image quality. The existing super-resolution image quality metrics are focused on specific features in the image and can effectively estimate the image quality with respect to that. Since super-resolution image quality metrics are focused and can’t estimate the overall image quality alone, it is suggested to utilise multi-metric evaluation strategies. The findings are highlighting the need for further research into multi-metric methodologies for synthetic aperture radar super-resolution.

Synteettisen apertuurin tutka on tutkakuvantamistekniikka, jolla voidaan tuottaa korkealaatuisia kuvia riippumatta säästä. Sen kyky toimia kaikissa sääolosuhteissa mahdollistaa monia hyödyllisiä käyttötarkoituksia. Synteettisen apertuurin tutkakuvissa on kuitenkin muutamia tyypillisiä ominaisuuksia, jotka aiheuttavat häiriöitä ja vaikeuttavat kuvien ymmärrettävyyttä. Häiriöt kuten speckle, layover ja diffusion huonontavat kuvan yleistä laatua ja vaikeuttavat kuvan tulkitsemista. Näiden vaikeuksien takia on kehitetty monia parantamismenetelmiä yksinkertaisista suodattimista aina syväoppimispohjaisiin superresoluutiomalleihin asti. Tällaisten menetelmien tehokkuuden arviointi on oleellista käytettävyyden parantamiseksi, ja sitä varten on kehitetty monia kuvanlaadun arviointimetriikoita. Monet näistä metriikoista on kuitenkin kehitetty optisia kuvia varten, eivätkä ne sovellu käytettäväksi yhtä hyvin synteettisen apertuurin tutkakuvien kanssa kuvantamismenetelmän ominaisuuksien takia. Tämä tutkielma keskittyy tutkimaan kuvanlaadun arviointimenetelmiä ja -metriikoita synteettisen apertuurin tutkakuvien yhteydessä. Tutkimus on tehty noudattamalla iteratiivisen kirjallisuuskatsauksen menetelmää, joka toimii jakamalla tutkimus iteratiivisesti suoritettaviin kierroksiin. Pääajatus on sisällyttää ja rajata lähteitä pois iteratiivisesti edeten siten, että joka kierroksella perehdytään lähteisiin yhä syvällisemmin. Kyseinen menetelmä mahdollistaa monien olemassa olevien tutkimusten käsittelyn lyhyen ajan kuluessa. Lähteiden haku tehdään avainsanojen avulla ja jokainen alateema käsitellään erikseen. Prosessin aikana esiin nousevat lähteet luokitellaan teemakohtaisiin kategorioihin. Työn löydökset viittaavat siihen, että synteettisen apertuurin tutkalle tyypilliset häiriöt aiheuttavat haasteita monen nykyisen metriikan hyödyntämiselle. Löydöksissä havaitaan myös, että mikään yksittäinen metriikka ei kykene arvioimaan superresoluutiokuvien laatua tehokkaasti, koska synteettisen apertuurin tutkalla on moninaisia käyttökohteita ja kuvanlaatuun liittyviä vaatimuksia. Nykyiset superresoluutiokuvien laadun mittarit keskittyvät kuvan tiettyihin piirteisiin ja pystyvät tehokkaasti arvioimaan laatua vain näiden osalta. Koska superresoluutiokuvien laadun mittarit ovat rajattuja eivätkä pysty yksin arvioimaan kokonaislaatua, suositellaan käytettäväksi useampaa rinnakkaista laadun metriikkaa. Työn tulokset nostavat esiin tarpeen lisätutkimukselle monimittaristen menetelmien kehittämiseksi synteettisen apertuurin tutkan superresoluutiota varten.
Keywords: radars; quality assessment; image quality; fi=Automaatio- ja tietotekniikka|en=Automation and Computer Science|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|